2013
DOI: 10.1007/s00795-013-0055-7
|View full text |Cite
|
Sign up to set email alerts
|

Diamine oxidase as a marker of intestinal mucosal injury and the effect of soluble dietary fiber on gastrointestinal tract toxicity after intravenous 5-fluorouracil treatment in rats

Abstract: The level of plasma diamine oxidase (DAO) activity is associated with the maturation and integrity of small intestinal mucosa. This study in rats investigated whether a decreased level of plasma DAO could reflect the severity of mucosal injury due to intravenous 5-fluorouracil (5-FU) treatment. The beneficial effect of soluble dietary fiber (SDF) on preventing diarrhea after 5-FU treatment was also examined. To induce diarrhea, 5-FU (50 mg/kg/day for four days) was administered via the tail vein with or withou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
87
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(91 citation statements)
references
References 16 publications
4
87
0
Order By: Relevance
“…When the bowel epithelial cells are damaged, this can lead to bowel barrier structural damage, so that villus epithelial cells will release significant quantities of DAO into the blood, leading to a rapid increase in DAO content. Thus, the DAO content in plasma directly reflects the damage to bowel epithelial cells and intestinal barrier structure, which is why it is measured[52-54]. We showed that the DAO content in plasma in the HCB group was significantly lower than those in the HB group, BM group, and NS group at the same postoperative time points, which confirmed that the degree of bowel function injury in the HCB group was ameliorated when compared with the other groups.…”
Section: Discussionsupporting
confidence: 60%
“…When the bowel epithelial cells are damaged, this can lead to bowel barrier structural damage, so that villus epithelial cells will release significant quantities of DAO into the blood, leading to a rapid increase in DAO content. Thus, the DAO content in plasma directly reflects the damage to bowel epithelial cells and intestinal barrier structure, which is why it is measured[52-54]. We showed that the DAO content in plasma in the HCB group was significantly lower than those in the HB group, BM group, and NS group at the same postoperative time points, which confirmed that the degree of bowel function injury in the HCB group was ameliorated when compared with the other groups.…”
Section: Discussionsupporting
confidence: 60%
“…The present data indicated that H 2 O 2 inhibited catalase, GSH-Px, and T-AOC activities and increased MDA levels, suggesting a signicant disruption in the oxidative balance aer exposure to H 2 O 2 treatment. 16 DAO is particularly abundant in enterocytes at the tip of small intestinal villi, from where it is released into the peripheral circulation and then inactivated in the liver. 3,14 Ingestion of H 2 O 2 changed the permeability and caused dysfunction in the intestine.…”
Section: Discussionmentioning
confidence: 99%
“…This is in agreement with several previous reports, which also demonstrated that H 2 O 2 caused a substantial reduction in GSH content associated with reduction in GPx activity. 11,16 Meanwhile, the high level of serum LPS is also considered to be the consequence of the increased intestinal permeability. Previous studies demonstrated that intragastric administration of 6% and 15% H 2 O 2 produced hemorrhagic and necrotic mucosal lesions in the fundic area in rats.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous investigations showed that the intestinal barrier function was damaged at the early weaning process of piglets (Smith et al., ; Hu et al., ; McLamb et al., ). d ‐lactic acid concentration and DAO activity in the plasma have been determined as circulating markers for monitoring the extent of intestinal barrier injury (Nielsen et al., ; Fukudome et al., ). Our current study indicated that dietary BA supplementation reduced plasma d ‐lactic acid concentration and DAO activity, which indicated that BA has beneficial effects on reducing intestinal permeability of piglets.…”
Section: Discussionmentioning
confidence: 99%